Contractor's liability to third party for defective works - Mohmad Zainordi, Zainab (2006)
In recent times, there have been increasing incidents of defective work in Malaysia and elsewhere due shoddy workmanship, cheating and sometimes, design errors. The consequences could be catastrophic and fatal as in collapsing buildings, and sometimes less dramatic, but no less catastrophic from a financial point of view. Most defects occur after the 18-month defect liability period but the problem arises when negligence action is brought by non-contracting party, who may be a subsequent owner of the building. With that in mind, that contractor’s liability does not stop with the contract and liability may rest in the field of torts: the objective of this research is determine the contractor’s liability to third party for defective works and look into the circumstances in which that the contractor liable or not liable towards those defects. The scope of this research is confined under conventional system where the contractor not involved in design and liability of contractor to third party in tort. The methodology of this research adopts from: the judicial decision of defective work (cases concerning contractor and third party), four-stage test and observation. After analyzing the data, the main findings signify the contractor’s liability to third party only in tort no duty in contract are, injury to third party, damage to property but not economic loss. As a conclusion with this research, a contractor owes a duty to exercise all ordinary and reasonable care and diligence in the performance of its work according to terms of contract; if he fails he is liable for resulting damages.